Lithuanian Conceptual Colour–Emotion Associations in the Global Context of 37 Nations - Domicelė Jonauskaitė (Psichologija)
Red with anger or green with envy – such metaphors link colours and emotions. While such colour metaphors vary across languages, conceptual associations between colours and emotions have many cross-cultural similarities. Here, we took published data from 8615 participants (2172 men) coming from 37 nations (i.e., Austria, Azerbaijan, Belgium, China, Colombia, Croatia, Cyprus, Egypt, Estonia, Finland, France, Georgia, Germany, Greece, India, Iran, Israel, Italy, Japan, Latvia, Lithuania, Mexico, Netherlands, New Zealand, Nigeria, Norway, Philippines, Poland, Russia, Saudi Arabia, Serbia, Spain, Sweden, Switzerland, Ukraine, United Kingdom, and United States) and analysed Lithuanian (n = 217) associations between colour terms and emotion concepts. Lithuanians had many associations, the most frequent being red–love, yellow–amusement, yellow–joy, and black–sadness (all endorsed by > 60% of participants). While Lithuanians associated more emotions with colours than the other participants, the Lithuanian pattern of these associations was highly similar to the global pattern (r = .92). When compared to each other nation individually, colour–emotion association pattern similarities ranged between .65 and .89. Lithuanian patterns were the most similar to the Russian and the least similar to the Egyptian ones. Crucially, such similarities could be predicted by linguistic but not geographic distances. Nations speaking languages linguistically closer to Lithuanian also displayed more similar colour–emotion association patterns. These results support universality of colour–emotion associations and point to small but meaningful cultural differences (e.g., red represented love more strongly than anger for Lithuanians but not globally). Future studies should look whether colours can modulate emotions, or whether such associations are purely abstract.